Multicomponent synthesis of artificial nucleases and their RNase and DNase activity - Gulevich, Anton V.; Koroleva, Lyudmila S.; Morozova, Olga V.; Bakhvalova, Valentina N.; Silnikov, Vladimir N.; Nenajdenko, Valentine G. (Beilstein Journal of Organic Chemistry, 2011)
The synthesis of new, artificial ribonucleases containing two amino acid residues connected by an aliphatic linker has been developed. Target molecules were synthesized via a catalytic three-component Ugi reaction from aliphatic diisocyanides. Preliminary investigations proved unspecific nuclease activity of the new compounds towards single-stranded RNA and double-stranded circular DNA.
Keywords: DNA; isocyanide; multicomponent reaction; organocatalysis; peptidomimetic; RNA